Pengaruh Peran Lembaga Pemberdayaan Masyarakat terhadap Pembangunan Jalan di Desa Lompotoo Kabupaten Bone Bolango - Swastiani Dunggio; Juriko Abdussamad; Zuchri Abdussamad (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
This study aims to examine the influence of the role of the Community Empowerment Institution (Lembaga Pemberdayaan Masyarakat/LPM) on village development, particularly village road development in Lompotoo Village, Suwawa District, Bone Bolango Regency. The study employed a survey method with a quantitative approach. The quantitative approach was used to address the research problem by describing and presenting the findings objectively. A questionnaire was utilized as the primary data collection instrument, and its validity and reliability were tested prior to analysis. The study involved a sample of 51 respondents. Data were analyzed using simple linear regression analysis. The results indicate that the role of the Community Empowerment Institution (LPM) has a significant effect on village road development, with a coefficient of determination (R²) of 0.625. This means that 62.5% of the variation in village road development (Y) can be explained by the role of the LPM (X), while the remaining 37.5% is influenced by other factors not examined in this study. Furthermore, the correlation coefficient (r) of 0.791 indicates a strong positive relationship between the two variables.